Pemahaman Terhadap Praktik Demokrasi Gen Z Pada Pemilihan Legislatif Tahun 2024 - Agustin Pratama Sihotang; Deo Agung Haganta Barus; Eirene Dahlia Sidabutar; Friska Lorentina Purba; Nasywa Yasmin Purba; Tesaa Lonika Simanullang (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Gen Z is an agent of change, so it is undeniable that strengthening political education as a preventive and educational effort is very important to be conveyed from an early age so that it is known and understood by generation Z. This study aims to find out the understanding of generation Z about the practice of legislative election democracy. This type of research is qualitative descriptive research. Descriptive research is research that aims to reveal existing facts and descriptive according to phenomena. The type of qualitative descriptive research is the disclosure and clarification of a phenomenon or social statement. The results of the study show that Gen Z has a fairly high level of political awareness. Many of them understand the importance of participation in legislative elections as a means to voice aspirations and determine the direction of state policy. This is driven by extensive access to information through social media and the internet, which provides them with a deeper knowledge of political issues and democratic processes.